Evaluation of lightweight fibreglass heel casts in the management of ulcers of the heel in diabetes: study protocol for a randomised controlled trial - Jeffcoate, William (Trials, 2014)
BACKGROUND: Ulcers of the heel in diabetes are the source of considerable suffering and cost. In the absence of specific treatments, it has been suggested that removable, lightweight fibreglass heel casts may both promote healing and reduce discomfort and pain. The aim of the study is to assess the effectiveness and cost-effectiveness of fibreglass heel casts in the management of heel ulcers. METHODS/DESIGN: This is an observer-blind, randomised controlled trial in which participants with diabetes and heel ulcers (NPUAP/EPUAP grades 2, 3 or 4 and present for 2 or more weeks) are randomised to receive either usual care plus lightweight fibreglass heel casts or usual care alone. Randomisation is undertaken by random number sequence generation incorporated as part of the electronic case record form, and is stratified by both ulcer area (less than versus equal to or greater than 1 cm(2)) and NPUAP/EPUAP grade. Participants are followed every two weeks until healing or for 24 weeks. The primary outcome measure is healing at or before 24 weeks and maintained for 4 weeks. Secondary outcomes include (i) ulcer-related outcomes: time to healing, change in ulcer area, minor and major amputation, secondary infection and (ii) patient-related outcomes: local pain, mood and function (EQ-5D), impact of the ulcer (Cardiff Wound Impact Schedule) and survival. Cost-effectiveness will be assessed using a decision analytic model to estimate costs from the perspective of the UK NHS and personal social services and health outcomes, including percent healing and Quality Adjusted Life Years gained. Safety will be documented as adverse and serious adverse device effects. DISCUSSION: If it is possible to confirm significant clinical benefit and/or cost-effectiveness, this would have direct implications for the management of this distressing and costly complication of diabetes TRIAL REGISTRATION NUMBER: ISRCTN62524796 Registered 29 March 2011